Revitalisasi Fungsi Sosial Masjid: Menjadikannya Sebagai Pusat Pelayanan Kesehatan di Lingkungan Masyarakat - Alvi Mahessa; Zainab Lailatil Zakir; Rahmi Dayati; Wismanto Wismanto; Yossy Pratiwi (Moral : Jurnal kajian Pendidikan Islam, 2024)
This article discusses the role of mosques as health centers in supporting community welfare. By utilizing existing infrastructure and communities, mosques can function as centers for education and health services. This research aims to explore the potential of mosques in improving public health through integrated health programs. The methods used in this research include literature reviews and interviews with ulama and health workers in several mosques. The research results show that the mosque has succeeded in holding various health activities, such as free health checks and health seminars, which the congregation responded positively to. In conclusion, mosques not only function as places of worship, but can also be effective health centers in strengthening people's physical and mental health.